Analysis of the Distribution of Health Workers and Health Facilities in Karanganyar Regency in 2022 - Annisaa Annisaa; Ema Novita Deniati (Universitas Negeri Malang, 2023)
Health, as one of the pillars of a nation's development, has an important role. This is in line with the understanding of the World Health Organization that there are 12 public health indicators as proxies for health indicators in the Sustainable Development Goals. However, in Karanganyar Regency, the typography is located on the slopes of Mount Lawu, and most of them are rural areas, resulting in an uneven distribution of health workers and health service facilities. Therefore, this study aims to determine the distribution of health workers in Karanganyar Regency so that it can be a concern in formulating policies regarding the distribution of health workers in urban and rural areas. This study uses secondary data collected from the 2022 Karanganyar Regency Health Human Resource Information System data and the 2022 Karanganyar Regency Health Office Health Profile data. From the analysis results, it is known that the ideal distribution of health workers in Karanganyar Regency is based on the national ratio and is still concentrated around the district government and areas close to urban areas.